2011
DOI: 10.1371/journal.pone.0027496
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Canonical Wnt/β-Catenin Signaling Activity by HCV Core Protein Promotes Cell Growth of Hepatocellular Carcinoma Cells

Abstract: BackgroundThe Hepatitis C virus (HCV) core protein has been implicated as a potential oncogene or a cofactor in HCV-related hepatocellular carcinoma (HCC), but the underlying mechanisms are unknown. Overactivation of the Wnt/β-catenin signaling is a major factor in oncogenesis of HCC. However, the pathogenesis of HCV core-associated Wnt/β-catenin activation remains to be further characterized. Therefore, we attempted to determine whether HCV core protein plays an important role in regulating Wnt/β-catenin sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 45 publications
3
99
2
1
Order By: Relevance
“…accumulation of ␤-catenin in human hepatoma cells (59,60). Furthermore, our findings suggest the critical involvement of HCV-induced OPN on the phosphorylation of Akt via ␣V␤3 and CD44 (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…accumulation of ␤-catenin in human hepatoma cells (59,60). Furthermore, our findings suggest the critical involvement of HCV-induced OPN on the phosphorylation of Akt via ␣V␤3 and CD44 (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Direct activation of the Wnt/β-catenin pathway was demonstrated in an in vitro model also separately for the core (C) protein of HCV [9,10,91]. HCVcore transfected Huh7 cells up-regulated Wnt-1 and WISP-2 transcription [91].…”
Section: Wnt/β-catenin Pathway In Hcv-associated Liver Carcinogenesismentioning
confidence: 89%
“…In both studies by Liu et al, core protein of HCV amplified the TCF-dependent transcriptional activity, intensified expression and stabilized β-catenin at the protein level in Huh7 cells through inactivation of GSK-3β. It proved to be responsible for amplification of cell proliferation and promotion of tumor growth following action of one of the Wnt pathway ligands, the Wnt-3a protein [9,10]. Core protein of HCV increases active β-catenin and nuclear accumulation in SMMC-7721 cells.…”
Section: Wnt/β-catenin Pathway In Hcv-associated Liver Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study also reported that the protein level of GSK3β is significantly lower in HCC tissues than in normal liver tissues and that reduced levels correlate with advanced clinicopathological characteristics and poorer prognosis [18]. In addition, both hepatitis B virus X protein and hepatitis C virus core protein activate the oncogenic Wnt pathway through the inactivation of GSK-3β [19,20]. As a direct inhibitor, GSK3β interaction protein (GSKIP) negatively regulates GSK3β and downstream Wnt signaling pathway, which is consistent with an oncogenic role of GSKIP in tumor growth [21].…”
Section: Introductionmentioning
confidence: 98%